Lire un blog: L’autofictif d’Eric Chevillard - Dominique Faria (Carnets)
Eric Chevillard is a writer who has published for the last twenty years at Les Editions de Minuit and who keeps a blog, L’Autofictif, since September 2007. The first year of the blog is going to be published in January 2009. We aim at grasping the differences between these two versions of the same work as well as the consequences they have on the process of reading and the pleasure that comes from it. This will allow us to see that, although their content is the same, each of these versions calls for a different kind of reading and produces different sorts of pleasures.